Comparison of the Effectiveness of Cognitive Behavioral Couple Therapy (CBT) and Intensive Short-Term Dynamic Psychotherapy for Couples (ISTDP) in Reducing Relationship Obsessive–Compulsive Disorder (ROCD) Symptoms and Improving Relationship Quality in Young Couples - Hosseini, Seyed Adel (Applied Family Therapy Journal (AFTJ), 2026)
Objective: This study aimed to compare the effectiveness of cognitive–behavioral couple therapy (CBT) and intensive short-term dynamic psychotherapy (ISTDP) in reducing relationship obsessive–compulsive disorder (ROCD) symptoms and improving relationship satisfaction among young couples. Methods and Materials: The study was conducted as a randomized controlled clinical trial with a pretest–posttest design, a control group, and a three-month follow-up. The statistical population consisted of young couples seeking psychological services due to relationship difficulties. A total of 52 couples (104 individuals) who met the inclusion criteria were selected and randomly assigned to three groups: CBT (18 couples), ISTDP (17 couples), and a wait-list control group (17 couples). The interventions were delivered in ten weekly 90-minute couple-based sessions following standardized protocols. Data were collected using the Relationship Obsessive–Compulsive Inventory (ROCI) and the Couples Satisfaction Index (CSI), with general obsessive–compulsive symptoms (OCI-R) and negative emotional states (DASS-21) included as covariates. Data were analyzed using multivariate analysis of variance (MANOVA) and multivariate analysis of covariance (MANCOVA) in SPSS version 27. Findings: MANOVA results indicated a significant multivariate effect of group on posttest ROCD symptoms and relationship satisfaction (p < .001), with large effect sizes. Univariate analyses showed significant between-group differences for both ROCD symptoms (F(2,101) = 139.75, p < .001) and relationship satisfaction (F(2,101) = 282.32, p < .001). Post hoc comparisons revealed that both CBT and ISTDP significantly outperformed the control group on both outcomes, while no substantial difference was observed between the two treatment groups in relationship satisfaction; ISTDP showed a marginally greater reduction in ROCD symptoms. MANCOVA results confirmed that these effects remained robust after controlling for OCI-R and DASS-21 (p < .001). Conclusion: Both CBT and ISTDP are highly effective couple-based interventions for reducing ROCD symptoms and enhancing relationship satisfaction, with comparable overall efficacy and strong clinical significance.